Pengaruh Kreativitas Guru Dan Motivasi Belajar Siswa Terhadap Hasil Belajar Ekonomi Siswa SMAN 1 Painan - Fitria Sofia; Dessyta Gumanti; Reni Respita (JURNAL ARMADA PENDIDIKAN, 2025)
This study aims to analyze the effects of teacher creativity and learning motivation on the economics learning outcomes of Grade X students at SMAN 1 Painan, both partially and simultaneously. The research employed a quantitative approach with a population of 296 students and a sample of 75 students selected through proportional random sampling. Data were collected using a questionnaire and analyzed using t-tests and an F-test. The results show that teacher creativity has a positive and significant effect on learning outcomes (β = 0.610; t_calculated = 2.490 > t_table = 1.933). Learning motivation also has a positive and significant effect on learning outcomes (β = 0.210; t_calculated = 2.812 > t_table = 1.933). Simultaneously, teacher creativity and learning motivation significantly affect economics learning outcomes (Sig. = 0.002 < 0.05; F_calculated = 6.361 > F_table = 3.124). These findings confirm that improving teacher creativity in instruction and strengthening students’ learning motivation contribute to better economics learning outcomes.